Review of the Flexible Credit Line, the Precautionary and Liquidity Line, and the Rapid Financing Instrument : Specific Proposals. (Policy Papers; Policy Paper ;, 2014)
This paper responds to Directors' request at the time of the February discussions of the Review of the Flexible Credit Line (FCL), the Precautionary and Liquidity Line (PLL) and the Rapid Financing Instrument (RFI) for further analysis focusing on three key issues: - The alignment of the FCL and PLL qualification criteria. The paper proposes a qualification framework for PLL arrangements based on the nine FCL criteria aiming to improve the transparency and predictability of PLL decisions, while maintaining the current qualification standards. The paper also proposes a refinement of the bank solvency criterion. - The operationalization of an external stress index. The paper proposes a methodology to calculate a new index to strengthen discussions of a country's external risks. Such an index would be presented to the Board at the time of requests for, or reviews under, FCL and PLL arrangements. - The use of indicators of institutional strength. The paper argues that a limited set of new institutional indicators could be used to help broaden the indicators of institutional strength already identified in the FCL and PLL Operational Guidance Notes.